CSR and RRI – overlapping or complementary management concepts? - Sudolska, Agata; Grego-Planer, Dorota (Contemporary organisation and management. Challenges and trends, 2020)
The growing attention on responsibility in business is forcing firms to build their competitiveness through integrating the principles of responsibility in their strategies. Given the necessity to apply new approaches in business, we focus on discussing two management concepts concerning responsibility: Corporate Social Responsibility and Responsible Research and Innovation. The aim of the paper is to explain these concepts, focusing on their similarities and differences as well as the possibility to integrate them into business practice. The research process is based on a literature review and focuses on providing a critical assessment of the reasons for integration CSR and RRI in a business context.